2011
DOI: 10.1128/cvi.05067-11
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of Teenagers with a Fifth Dose of Reduced DTaP-IPV Induces High Levels of Pertussis Antibodies with a Significant Increase in Opsonophagocytic Activity

Abstract: Waning vaccine-induced immunity against Bordetella pertussis is observed among adolescents and adults. A high incidence of pertussis has been reported in this population, which serves as a reservoir for B. pertussis. A fifth dose of reduced antigen of diphtheria-tetanus-acellular-pertussis and inactivated polio vaccine was given as a booster dose to healthy teenagers. The antibody activity against B. pertussis antigens was measured prior to and 4 to 8 weeks after the booster by different assays: enzyme-linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…It may thus be argued that such left-over sera may not be representative for the general population regarding the immune response against pertussis following infection or vaccination. However, the peak response observed in this study is very similar to what we observed in a previous vaccine study [17] Such left-over samples are often used for these kinds of studies, as in a recent seroprevalence study of pertussis involving sixteen European countries (Organization of a sereoprevalence study of pertussis in the member states and EEA countries (WP6); Specific Contract ECDC/2011/013). Sera from children where the medical record indicated possible immunodeficiency were excluded.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…It may thus be argued that such left-over sera may not be representative for the general population regarding the immune response against pertussis following infection or vaccination. However, the peak response observed in this study is very similar to what we observed in a previous vaccine study [17] Such left-over samples are often used for these kinds of studies, as in a recent seroprevalence study of pertussis involving sixteen European countries (Organization of a sereoprevalence study of pertussis in the member states and EEA countries (WP6); Specific Contract ECDC/2011/013). Sera from children where the medical record indicated possible immunodeficiency were excluded.…”
Section: Discussionsupporting
confidence: 79%
“…The lower limit of detection was 1 IU/ml, and sera with values below this were assigned a value of 1 IU/ml. IgG antibodies against pertactin (Prn) (RIVM, the Netherlands) were measured with a similar method as for the anti-PT IgG, with a Prn coat at 1 g/ml [17]. The sera were diluted in four two-fold dilutions and the results were calculated against the WHO reference serum 06/140, containing 65 IU/ml anti-Prn IgG by the use of four-parameter curve analysis.…”
Section: Serological Analysismentioning
confidence: 99%
“…It is possible that increased activation of cellular components may also enhance the response to polio vaccine. The booster response to a fifth dose of combination vaccine that included DTaP and IPV was evaluated by Aase et al [22] in healthy teenagers, and although these investigators did not report the effect on polio responses, they documented a significant increase in IgG levels and opsonophagocytosis to pertussis. Thus, the combination does not hinder the responses to pertussis antigens.…”
Section: Discussionmentioning
confidence: 98%
“…In line with that, it was shown that a fifth dose of a 3-component aP vaccine when given to teenagers to boost previous immunizations significantly improves opsonophagocytic activity against B. pertussis [95]. The increased opsonophagocytosis was accompanied by increased IgG binding to live bacteria and correlated with high levels of IgG antibodies anti-PRN, -FHA and -PT [95].…”
Section: Complement-mediated Bacterial Killing and Vaccine-induced Protmentioning
confidence: 61%